2015
DOI: 10.1007/s10803-015-2630-3
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Awareness of Facial Affect in Higher-Functioning Children and Adolescents with Autism Spectrum Disorder

Abstract: Higher-functioning participants with and without autism spectrum disorder (ASD) viewed a series of face stimuli, made decisions regarding the affect of each face, and indicated their confidence in each decision. Confidence significantly predicted accuracy across all participants, but this relation was stronger for participants with typical development than participants with ASD. In the hierarchical linear modeling analysis, there were no differences in face processing accuracy between participants with and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
28
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 77 publications
(156 reference statements)
4
28
1
2
Order By: Relevance
“…Alternatively, in standard judgement of confidence (JOC) tasks participants are typically asked to make retrospective judgements assessing how confident they are that their answer to a question is correct. The few existing studies of metacognitive monitoring in ASD have suggested that individuals with this disorder demonstrate diminished accuracy when making both feeling of knowing judgements (Grainger et al 2014 ; Wojcik et al 2013 ) and judgments of confidence (Grainger et al 2016 ; Wilkinson et al 2010 ; Brosnan et al 2015 ; McMahon et al 2016 ; but see Sawyer et al 2014 ). That is, the correspondence between participants’ predictions about their own memory performance and their actual memory performance appears to be lower among individuals with ASD than among neurotypical individuals, when making these types of metacognitive judgments.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, in standard judgement of confidence (JOC) tasks participants are typically asked to make retrospective judgements assessing how confident they are that their answer to a question is correct. The few existing studies of metacognitive monitoring in ASD have suggested that individuals with this disorder demonstrate diminished accuracy when making both feeling of knowing judgements (Grainger et al 2014 ; Wojcik et al 2013 ) and judgments of confidence (Grainger et al 2016 ; Wilkinson et al 2010 ; Brosnan et al 2015 ; McMahon et al 2016 ; but see Sawyer et al 2014 ). That is, the correspondence between participants’ predictions about their own memory performance and their actual memory performance appears to be lower among individuals with ASD than among neurotypical individuals, when making these types of metacognitive judgments.…”
Section: Introductionmentioning
confidence: 99%
“…Five studies have explored the accuracy of JOC in children with ASD, three of which have observed diminished accuracy relative to comparison participants (Grainger et al, 2016;McMahon et al, 2016;Wilkinson et al 2010; but see Sawyer et al, 2013, andWojcik et al, 2011) One effect studied in relation to JOC accuracy (but which has never been explored in ASD) is the "hypercorrection effect". When young neurotypical adults (e.g., Butterfield & Mangels, 2006) and children (Metcalfe & Finn, 2012) report high confidence in answers that turn out to be incorrect, their memory for the correct answer is subsequently enhanced, suggesting that monitoring of one's confidence mediates learning.…”
mentioning
confidence: 99%
“…In subsequent development, it is used to refer to cognition about cognition: thinking about your own thinking [2]. Metacognition includes two domains: knowledge of cognition and regulation of cognition [3], [4]. Meanwhile, according to Arthur et al, metacognition falls into metacognitive knowledge and experience [2].…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of cognition is the major part of metacognition [4], [6]- [9] which refers to the abilities to manage and control an individual's own cognition [3]. It involves a set of mental activities that help students control their learning process [9], and is associated with the monitoring and redirection of one's activities during the course of reading to reach the desired goals [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation